Prophylactic rivaroxaban in the early post-discharge period reduces the rates of hospitalization for atrial fibrillation and incidence of sudden cardiac death during long-term follow-up in hospitalized COVID-19 survivors - Fiedler, Lukas; Motloch, Lukas J.; Dieplinger, Anna-Maria; Jirak, Peter; Davtyan, Paruir; Gareeva, Diana; Badykova, Elena; Badykov, Marat; Lakman, Irina; Agapitov, Aleksandr; Sadikova, Liana; Pavlov, Valentin; et al. (Frontiers in Pharmacology, 2023)
Introduction: While acute Coronavirus disease 2019 (COVID-19) affects the cardiovascular (CV) system according to recent data, an increased CV risk has been reported also during long-term follow-up (FU). In addition to other CV pathologies in COVID-19 survivors, an enhanced risk for arrhythmic events and sudden cardiac death (SCD) has been observed. While recommendations on post-discharge thromboprophylaxis are conflicting in this population, prophylactic short-term rivaroxaban therapy after hospital discharge showed promising results. However, the impact of this regimen on the incidence of cardiac arrhythmias has not been evaluated to date. Methods: To investigate the efficacy of this therapy, we conducted a single center, retrospective analysis of 1804 consecutive, hospitalized COVID-19 survivors between April and December 2020. Patients received either a 30-day post-discharge thromboprophylaxis treatment regimen using rivaroxaban 10mg every day (QD) (Rivaroxaban group (Riva); n=996) or no thromboprophylaxis (Control group (Ctrl); n=808). Hospitalization for new atrial fibrillation (AF), new higher-degree Atrioventricular-block (AVB) as well as incidence of SCD were investigated in 12-month FU [FU: 347(310/449) days]. Results: No differences in baseline characteristics (Ctrl vs. Riva: age: 59.0 (48.9/66.8) vs. 57 (46.5/64.9) years, p=n.s.; male: 41.5% vs. 43.7%, p=n.s.) and in the history of relevant CV-disease were observed between the two groups. While hospitalizations for AVB were not reported in either group, relevant rates of hospitalizations for new AF (0.99%, n=8/808) as well as a high rate of SCD events (2.35%, n=19/808) were seen in the Ctrl. These cardiac events were attenuated by early post-discharge prophylactic rivaroxaban therapy (AF: n=2/996, 0.20%, p=0.026 and SCD: n=3/996, 0.30%, p<0.001) which was also observed after applying a logistic regression model for propensity score matching (AF: χ2-statistics= 6.45, p=0.013 and SCD: χ2-statistics=9.33, p=0.002). Of note, no major bleeding complications were observed in either group. Conclusion: Atrial arrhythmic and SCD events are present during the first 12 months after hospitalization for COVID-19. Extended prophylactic Rivaroxaban therapy after hospital discharge could reduce new onset of AF and SCD in hospitalized COVID-19 survivors.